A hybrid linguistic fuzzy multiple criteria group selection of a chief accounting officer - Keršulienė, Violeta; Turskis, Zenonas (Journal of Business Economics and Management, 2014)
In the preceding decade, economic and social costs brought by financial statement fraud have shaken markets, devastated investment portfolios and reduced confidence in financial reporting. A financial department is special in the way it needs to conform to standards. Many individual attributes considered for the selection of a chief accounting officer, such as organisational skills, personality, leadership etc. This paper focuses on a fuzzy multi-criteria decision making (MCDM) algorithm, which integrates the principles of fusion of fuzzy information, additive ratio assessment method with fuzzy numbers (ARAS-F), fuzzy weighted-product model and analytic hierarchy process (AHP). The proposed method is apt to manage information assessed using both linguistic and numerical scales in a decision making problem with a group of information sources. The computational procedure is illustrated through the problem related to the selection of a chief accounting officer.